2022
DOI: 10.1021/acs.jmedchem.2c00271
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 8-(6-Methoxypyridin-3-yl)-1-(4-(piperazin-1-yl)-3-(trifluoromethyl)phenyl)-1,5-dihydro-4H-[1,2,3]triazolo[4,5-c]quinolin-4-one (CQ211) as a Highly Potent and Selective RIOK2 Inhibitor

Abstract: RIOK2 is an atypical kinase implicated in multiple human cancers. Although recent studies establish the role of RIOK2 in ribosome maturation and cell cycle progression, its biological functions remain poorly elucidated, hindering the potential to explore RIOK2 as a therapeutic target. Here, we report the discovery of CQ211, the most potent and selective RIOK2 inhibitor reported so far. CQ211 displays a high binding affinity (K d = 6.1 nM) and shows excellent selectivity to RIOK2 in both enzymatic and cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Molecular docking studies revealed interactions within the ATP binding site on RIO kinase, allowing for a targeted optimization process that led to the preparation of compound CQ211, characterized by high potency (K d = 6.1 nM) and excellent selectivity profile against this atypical kinase (Figure 3). [48] Triazoloquinazolinones 71 have been obtained through a reaction between terminal alkynes 14 and 2-azido-N-methoxybenzamides 70 (Scheme 25 and 26). [49] In this case as well, the best catalyst remains CuI, along with DIPEA, in THF in the presence of air.…”
Section: Intramolecular Interrupted Click Reactionsmentioning
confidence: 99%
“…Molecular docking studies revealed interactions within the ATP binding site on RIO kinase, allowing for a targeted optimization process that led to the preparation of compound CQ211, characterized by high potency (K d = 6.1 nM) and excellent selectivity profile against this atypical kinase (Figure 3). [48] Triazoloquinazolinones 71 have been obtained through a reaction between terminal alkynes 14 and 2-azido-N-methoxybenzamides 70 (Scheme 25 and 26). [49] In this case as well, the best catalyst remains CuI, along with DIPEA, in THF in the presence of air.…”
Section: Intramolecular Interrupted Click Reactionsmentioning
confidence: 99%
“…Thus, development of efficient methods for the construction of 1,2,3-triazole fused heterocycles with substitution diversity is highly appealing. As part of our efforts to develop novel tandem reactions for the construction of fused 1,2,3-triazole compounds, 12 herein we would like to report a transition-metal-free [3 + 2] cycloaddition/intramolecular hydroamination tandem reaction of sodium azide with N -(prop-2-yn-1-yl)propiolamides for the formation of [1,2,3]triazolo [1,5- a ]pyrazin-4(5 H )-ones (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we have identified a class of [1,2,3] triazolo [4,5-c]quinolin-4-one compounds as novel RIOK2 inhibitors. 20,21 The representative compound 7 (CQ211, Fig. 1) displayed high binding affinity (K d = 6.1 nM) and showed excellent selectivity to RIOK2 in both enzymic and cellular studies.…”
Section: Introductionmentioning
confidence: 99%